Higher-derivative non-Abelian gauge fields via the Faddeev-Jackiw formalism - Bufalo, R. [UNESP]; Pimentel, B. M. [UNESP] (Springer, 2014)
In this paper we analyze two higher-derivative theories, the generalized electrodynamics and the Alekseev-Arbuzov-Baikov effective Lagrangian from the point of view of the Faddeev-Jackiw symplectic approach. It is shown that the full set of constraints is obtained directly from the zero-mode eigenvectors, and that they are in accordance with well-known results from Dirac's theory, a recurrent issue in the literature. The method shows to be rather economical in relation to the Dirac one, obviating thus unnecessary classification and calculations. Afterwards, to conclude we construct the transition amplitude of the non-Abelian theory following a constrained BRST method.